Ethnomathematics and Cultural Project-Based Learning: Exploring Students’ Experiences (Pragyaratna प्रज्ञारत्न, 2025)
Mathematics pervades all aspects of human life, offering valuable skills and knowledge for various activities. Encouraging students to explore mathematical concepts in their surroundings is a powerful means of fostering genuine comprehension of formal mathematics. Unfortunately, the absence of context-driven learning poses challenges for students in grasping mathematics meaningfully. This study intends to explore students’ perception on the use of cultural project-based learning approach. The research involves twenty girls and ten boys from grade 9D, and two teachers participated to facilitate students in cultural project-based learning. Qualitative data are gathered through questionnaires and observations. The insights and outcomes of this research held the potential to benefit educators, trainers, and researchers in advancing meaningful mathematics instruction. Additionally, it promises to bolster project-based learning in mathematics. The ladder project notably demonstrates that students enthusiastically recognize the pervasive presence of mathematical concepts in daily life.